Aspectos da Arquitetura e Implementação de um Sistema de Proveniência no Contexto de Workflows Científicos - Oliveira, Claudson; Gaspar, Wander; Braga, Regina; Souza, Jairo (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
This paper presents the architecture and implementation of a data provenance system in the field of scientific experiments processed in collaborative research environments. The text highlights the contribution of basic scientific research to the project and tangible bene ts for undergraduate students.